#### Answer

$3x-2$

#### Work Step by Step

Add the two terms from one another.
$(2x+3)+(x-5) = 2x+x+3-5 = 3x-2$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$3x-2$

Add the two terms from one another.
$(2x+3)+(x-5) = 2x+x+3-5 = 3x-2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.